Enterprise information architectures (EIAs), interoperability frameworks, maturity models: uma revisão de literatura (Advances in Knowledge Representation, 2023)
This article aims to present a literature review about enterprise information architectures (EIAs) designed in the last five decades and the most relevant interoperability frameworks that followed them, applied to the business, governmental, industrial, and military defense scopes. It was sought to know the particularities of each solution and the strategies adopted to enable the exchange of data, information, and knowledge in critical domains for society, from its intermediary. In summary, 31 interoperability frameworks and 28 related maturity models were identified. The review presented here is an integral part of doctoral research carried out in the field of Information Science that investigated ontology-oriented semantic interoperability in a case study in the energy domain. The article begins a series of publications where it is intended to discuss the contributions that can come from the adoption of formal ontologies for the design of well-founded ontological frameworks in contrast to the solutions investigated in this review.